Potential impacts of climate-related decline of seafood harvest on nutritional status of coastal First Nations in British Columbia, Canada. - Lesya Marushka; Tiff-Annie Kenny; Malek Batal; William W L Cheung; Karen Fediuk; Christopher D Golden; Anne K Salomon; Tonio Sadik; Lauren V Weatherdon; Hing Man Chan (PLOS ONE, 2019)
BACKGROUND:Traditional food systems are under pressure from various stressors, including climate change which is projected to negatively alter the abundance of marine species harvested by coastal First Nations (FNs) in British Columbia (BC). OBJECTIVE:To model the potential impacts of the climate-related declines in seafood production on the nutritional status of coastal BC FNs. In addition, we projected potential changes in nutrient intakes, under different scenarios of substitution where traditional seafood is replaced with alternative non-traditional foods. METHODS:The study design is a mixed-method approach that combines two datasets: projected scenarios of climate-related change on seafood catch potential for coastal BC FNs and data derived from the cross-sectional First Nations Food, Nutrition, and Environment Study. The consumption of seafood was estimated using a food frequency questionnaire among 356 FNs. The contribution of seafood consumption to protein, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), vitamins (A, B12, D, niacin), and minerals (zinc, selenium and iron) requirements was assessed using Dietary Reference Intakes (DRIs). RESULTS:Traditional seafood consumption provided daily recommendations of EPA+DHA (74-184%) and vitamin B12 (84-152%) and substantial levels of niacin (28-55%), selenium (29-55%), vitamin D (15-30%) and protein (14-30%). Projected climate change was estimated to reduce the intakes of essential nutrients by 21% and 31% under 'strong mitigation' (Representative Concentration Pathway, RCP2.6) and 'business-as-usual' (RCP8.5) climate change scenarios, respectively, by the year 2050 relative to 2000. The hypothetical substitution of seafood with selected alternative non-traditional foods does not provide adequate amounts of nutrients. CONCLUSION:Traditionally-harvested seafood remains fundamental to the contemporary diet and health of coastal BC FNs. Potential dietary shifts aggravated by climate-related declines in seafood consumption may have significant ...